Insularity, Travel, and the Encounter with Female Alterity in Cervantes’s Los Trabajos de Persiles y Sigismunda - Mattioli, Laura (Status Quaestionis, 2023)
The Persiles exploits a dialectic of centre and periphery to mark the difference between the known, Christian world and the strange, “other” spaces situated on the margins of the euro-centric map. This paper argues that Cervantes knowingly exploits the still largely unexplored Northern regions to situate the portrayal of the female other. Through the experience of travel, the two princes and their companions meet types of women that diverge from the model of the idealised lady, represented by Auristela: desiring women, evil ones and courageous others populate the universe of the Far North. Although some of these representations flow into the monstrous and suffer condemnation from the narrator, Cervantes does not aim to deprecate alterity; instead, he uses the Northern settings to illustrate the varied facets of the female subject.